Team idiosyncratic deals and team breakthrough innovation: Based on the perspective of input-process-output model - Fan, Zili; Sun, Hao; Wang, Lijun; Zhu, Mengting; Peng, Ting (Frontiers in Psychology, 2022)
Purpose: As a new human resource management practice, team idiosyncratic deals play an important role in attracting, retaining and motivating employees to promote breakthrough innovation. Based on the I-P-O model, this study examines the impact of team idiosyncratic deals on team breakthrough innovation through team exploratory-exploitative knowledge sharing, and the moderating role of team transactive memory systems and team cognitive flexibility in this process. Participants and Methods: In order to reduce the effects of common method biases and causal lag effect, this study is divided into three stages for data collection, with a time interval of 1 month. 80 teams (406 employees) from six enterprises in Shanghai and Hangzhou were selected as samples, and the hypothesis test was carried out by hierarchical regression analysis, bootstrap and Johnson-Neyman method. Results: The results show that team idiosyncratic deals have a positive impact on team breakthrough innovation through team exploratory-exploitative knowledge sharing, and that team transactive memory systems and team cognitive flexibility positively moderate the mediating effect of team exploratory-exploitative knowledge sharing between team idiosyncratic deals and team breakthrough innovation in the first stage and the second stage, respectively. Under the joint effect of high team transactive memory systems and high team cognitive flexibility, team idiosyncratic deals have a stronger indirect effect on team breakthrough innovation through team exploratory-exploitative knowledge sharing. Conclusion: The research results break through the previous research framework of social exchange theory, and I-P-O model to explore the influence mechanism of team idiosyncratic deals, in order to promote the sustainable growth of team breakthrough innovation through this non-standard work arrangement. It is hoped that this research can inspire modern enterprises to create team idiosyncratic deals for core teams engaged in breakthrough innovation, which are more conducive to give full play to their heterogeneous talents, and finally help enterprises break through the industry bottleneck and win the market competition.